Mulheres em trânsito interseccional: investigando o território religioso de Juazeiro do Norte/CE - Silva, Ana Clara Benjamim (2025)
Urban space, although often perceived as neutral, is profoundly shaped by patriarchal norms and power structures, imposing barriers on women that transcend physical limitations and highlight inequalities in access, appropriation, and a sense of belonging to the city. Furthermore, women do not constitute a homogeneous collective, and it is through an intersectional approach that it becomes possible to understand how their urban experiences are shaped by local dynamics and the multiple social markers that permeate them. Within the scope of these reflections, the research investigates the movement of women in a territory characterized by the intense presence of religiosity, taking as a spatial focus the central area of Juazeiro do Norte, in the state of Ceará/Brazil. The analysis, guided by a gender approach, made it possible to highlight both the ways in which the urban environment shapes women's experiences and the ways in which women, in their daily activities, transform this space, configuring disputes between consolidated traditions, social movements of a transformative nature, and challenges to patriarchal hierarchies. The methodological approach faced the challenge of articulating these multiple dimensions, using strategies such as the interpretative resource of literary texts, the adoption of participatory workshops, field observations and semi-structured interviews. The results of the research indicate that, in Juazeiro do Norte, the forms of oppression against women go beyond the deficiencies of the urban infrastructure, being sustained by social and cultural norms associated with religiosity and the dynamics of pilgrimages. This is an environment deeply marked by a syncretic Catholicism, whose influence on the construction of female identity is significant, generating constant tensions between religious values, cultural norms and daily social practices. In this context, gender violence is expressed, among other ways, through practices of control and behavioral discrimination, which limit women's mobility and restrict their access to resources and economic opportunities.